The ECSI model in higher education in tourism: a segmentation analysis in the Portuguese case - Eurico, S.; Pinto, P.; Silva, J. A.; Marques, C. (Tourism, 2018)
This research explores the European Consumer Satisfaction Index model applied to higher education in tourism by including the construct of employability and by accounting for unobserved heterogeneity. In particular, it intends to identify segments of higher education institutions' (HEI) consumers based on the structural model estimates of the European Consumer Satisfaction Index (ECSI), enlarged with the employability construct. A model-based segmentation approach using FIMIX in PLS path model-ling is used. Th e ECSI is properly adjusted to the educational framework and shows its effectiveness when assessing students' satisfaction regarding the attended HEI. Two distinctive graduate segments are identifi ed using a sample of 166 HEI consumers. The results confi rm the assumption of heterogeneity as the relationships differ across segments and the need for HEIs to target those segments differently in such a competitive context.